Clinical characteristics, risk factors, and incidence of symptomatic coronavirus disease 2019 in a large cohort of adults living with HIV: a single-center, prospective observational study. (1st October 2020) - Inciarte, Alexy; Gonzalez-Cordon, Ana; Rojas, Jhon; Torres, Berta; de Lazzari, Elisa; de la Mora, Lorena; Martinez-Rebollar, Maria; Laguno, Montserrat; Callau, Pilar; Gonzalez-Navarro, Azucena; Leal, Lorna; Garcia, Felipe; et al.
Abstract : Background: It is unclear how characteristics, risk factors, and incidence of coronavirus disease 2019 (COVID-19) in people living with HIV (PLWH) differ from the general population. Methods: Prospective observational single-center cohort study of adult PLWH reporting symptoms of COVID-19. We assessed clinical characteristics, risk factors for COVID-19 diagnosis and severity, and standardized incidence rate ratio for COVID-19 cases in PLWH cohort and in Barcelona. Results: From 1 March 2020 to 10 May 2020, 53 out of 5683 (0.9% confidence interval 0.7–1.2%) PLWH were diagnosed with COVID-19. Median age was 44 years, CD4 + T cells were 618/μl and CD4 + /CD8 + was 0.90. All but two individuals were virologically suppressed. Cough (87%) and fever (82%) were the most common symptoms. Twenty-six (49%) were admitted, six (14%) had severe disease, four (8%) required ICU admission, and two (4%) died. Several laboratory markers (lower O2 saturation and platelets, and higher leukocytes, creatinine, lactate dehydrogenase, C reactive protein, procalcitonin, and ferritin) were associated with COVID-19 severity. No HIV or antiretroviral-related factors were associated with COVID-19 diagnosis or severity. Standardized incidence rate ratios of confirmed or confirmed/probable COVID-19 in PLWH were 38% (95% confidence interval 27–52%, P < 0.0001) and 33% (95% confidence interval 21–50%, P < 0.0001), respectively relative to the general population. Conclusion: PLWH with COVID-19 did not differ from the rest of the HIV cohort. Clinical presentation, severity rate, and mortality were not dependent on any HIV-related or antiretroviral-related factor. COVID-19 standardized incidence rate was lower in PLWH than in the general population. These findings should be confirmed in larger multicenter cohort studies. Abstract : Supplemental Digital Content is available in the text